(3eUMa TQjas ((3jGbhJ GdeSJYUei s)
(3ChdgG (B:s
(3ShQI GdHbQI Bde Pdc GdcJGH dGQjH ajg gOi ddeJbjf s
(3BNQgG (B:s
"(3ShQI GdfGS(B" (3jhShS ai UOhQ GdfGS ef GdLfI hGdfGS MGeOkG ddg JYGdi Ydi fYeJg s
(3HYV GdCjGJ hGdShQ ef GdbQBf GdcQje efgG GdHbQg , Gdajd ,, GdfGS , s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcJH GdSeGhjIs